Model Solusi Efektif Stabilitas Pasar Syariah - Nurhayadi, Yadi; Rito, Rito; Al-Azizah, Ummu Salma (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2018)
The Research will confirm that the differences between the Islamic Economic System and the Conventional Economic System should generate differences between the sharia market and the conventional market. Conventional Market clearly is influenced by banking interest rate, speculation, and permit gambling, disobedience, and other bussiness that are prohibited by Islamic values. However, Sharia Market should be free from banking interest rates, speculation, and not permit gambling, disobedience, and other bussiness that are prohibited by Islamic values. Through bivariate and multivariate analysis, the research conducted regression, correlation, and determination test to know whether conventional market influence on sharia market. The analysis is based on the investigation of Indonesia Stock Exchange datas from December 2006 to May 2017. In these cases, Jakarta Stock Exchange (JSX) Composite Index (Indeks Harga Saham Gabungan (IHSG)) and Jakarta Stock Exchange Liquid Index (LQ45) are classified as conventional market. Meanwhile, Sharia Market is represented by Jakarta Islamic Index (JII) dan Indonesia Sharia Stock Index (ISSI). The results show that Conventional Market has a strong and positive correlation with Sharia Market, which indicates that sharia market runs together with conventional market with the same character, in other words sharia market is still influenced mainly by banking interest rate and speculation. The research will observe specifically at the fluctuations of sharia stocks at JII and ISSI compared with the fluctuations of conventional stocks on IHSG and LQ45. The reseach quantitative methods are Least Square Bivariate Analysis dan Multivariate Analysis, serta Pearson product-moment correlation and determination coefficient. The next steps, the research will also accurately investigate the list of issuers on IHSG, LQ45, JII, and ISSI, and compare the specific sharia issuers with non-sharia issuers, so that the classification of IHSG and LQ45 as conventional market is corrected. Based on the results of the analysis of regression, correlation, determination, and investigation of datas, the research will formulate model of effective solution of sharia market stability.